Making the Business Case for Evidence-Based Practice and Nurse/Clinician Well-Being to Improve Health Care Quality, Safety, Patient Outcomes, and Costs - Melnyk, Bernadette Mazurek; Hsieh, Andreanna Pavan (Nurse leader, 2025)
American health care is high in costs and poor in population health and well-being outcomes. Although engaging in evidence-based practice (EBP) and promoting nurse/clinician well-being improves quality of care, lessens medical errors, and enhances patient outcomes, they are not consistent norms. Top leadership drives an organization’s vision, mission, values, day-to-day functioning, and culture, which impacts clinicians’ well-being and how they practice. EBP and nurse/clinician well-being is the magic formula for achieving healthcare quality and safety, yet they do not receive much financial investment. This article highlights return on investment for EBP and nurse/clinician well-being and emphasizes key strategies for their success.